2018
DOI: 10.2105/ajph.2017.304277
|View full text |Cite
|
Sign up to set email alerts
|

The Inverse Equity Hypothesis: Analyses of Institutional Deliveries in 286 National Surveys

Abstract: Objectives. To test the inverse equity hypothesis, which postulates that new health interventions are initially adopted by the wealthy and thus increase inequalities-as population coverage increases, only the poorest will lag behind all other groups.Methods. We analyzed the proportion of births occurring in a health facility by wealth quintile in 286 surveys from 89 low-and middle-income countries and developed an inequality pattern index. Positive values indicate that inequality is driven by early adoption b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 40 publications
8
96
0
3
Order By: Relevance
“…It proposes that it is the wealthier segments of a population who would initially adopt newly introduced health interventions, increasing absolute inequalities in health, leaving those with a higher vulnerability lagging. Recent research has shown this hypothesis to be true for inequalities in population coverage for institutional deliveries (Victora et al 2018), and this might also be the case for smoking policies.…”
Section: Discussionmentioning
confidence: 92%
“…It proposes that it is the wealthier segments of a population who would initially adopt newly introduced health interventions, increasing absolute inequalities in health, leaving those with a higher vulnerability lagging. Recent research has shown this hypothesis to be true for inequalities in population coverage for institutional deliveries (Victora et al 2018), and this might also be the case for smoking policies.…”
Section: Discussionmentioning
confidence: 92%
“…As currently proposed, the index relies on prevalence by wealth quintiles (rather than deciles). It is expressed in percent points, and calculated according to the formula below, where PQ1 stands for prevalence in the poorest quintile, PQ5 prevalence in the richest quintile, and PN the national prevalence [17].…”
Section: Methodsmentioning
confidence: 99%
“…Our present analyses cover both ends of the malnutrition spectrum in women-underweight and overweight or obesity-in a larger number of LMICs than available in earlier studies. In addition to describing the magnitude of socioeconomic inequalities using summary indices, we report on the inequality pattern index, that is, on whether such inequalities are being primarily driven by the poorest or richest groups of women [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite strong technical guidance and recommendations for age‐appropriate IYCF practices for children below 2 years (Pan American Health Organization, ; World Health Organization [WHO], ), global progress on these practices has been slow. Socio‐economic inequalities in malnutrition and access to effective nutrition and health services continue to exist throughout the world (Black et al, ; Victora et al, ; Victora & Somers, ). Children living in resource‐poor settings are generally at a greater disadvantage than their wealthier counterparts with respect to living conditions, access to preventive care and complementary feeding practices (Barros, Victora, Scherpbier, & Gwatkin, ), although poorer households are often more likely to breastfeed and to do so for longer periods of time.…”
Section: Introductionmentioning
confidence: 99%